Improvement of Data Security Using Mixcolumn - Singh Poja Ramesh; Santhosh Kumar Singh (Institute of Advanced Engineering and Science, 2018)
Advanced Encryption Standard is the security based algorithm used to protect the data from the attackers.In this paper, Optimized Inverse MixColumn transformation has been designed with the help of Xtime multiplication process. Xtime multiplication performs the multiplication function for ‘m X m’ data; results will be m-bit data. Further the complexity of Xtime multiplication process has been identified and re-designed with the help of effective CSE techniques. Developed Reduced Xtime based optimized Inverse MixColumn transformation provide better performances than traditional Xtime based Inverse MixColumn multiplication.